Artificial Insemination of Beef Cattle UPSUS SIWAB Program Based on the Calculation of Non-Return Rate, Service Per Conception and Calving Rate In The North Kayong Regency - Duta Setiawan (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
This study aims to Determine the success rate of the Artificial Insemination in North Kayong Regency of West Kalimantan Province roomates has been done by IB officers. Artificial insemination is the process of introduction or delivery of cement into the genitals of female cows by means of made devices. North Kayong districts Regency is one of the which is administratively established Republic of Indonesia based on Law no. 6 of 2007 is an area that is developing cattle. The location that Became the focus of the evaluation of the success of Artificial Insemination is in three districts of Maya Island district, Sukadana and Seponti. Data used in this research is secondary Data Obtained from inseminator. The parameters used in this evaluation are the Non Return Rate (NRR), Service per Conception (S / C) and Calving Rate (CvR). The results Showed that the average of the three sub-districts in North Kayong district was for the highest 90% NRR in Sukadana district and the Lowest score of 67% in the Mayan Island district. S / C Obtained the highest number of 3.4 in Maya Island district and the Lowest S / C number district of Seponti 1.8. The highest score was 92% CvR in Sukadana district and the cancel CvR score was 64% in the Mayan Island district. The Conclusions Obtained based on the value of NRR, S / C, and CvR on artificial insemination evaluation with the best artificial insemination implementation are Sukadana district, followed by district of Seponti and last is Maya Island district.